MODEL BISNIS AGROFARM CIANJUR (Studi Kasus Kelompok Tani Agro Segar pada P4S Agrofarm Cianjur, Desa Ciherang, Kabupaten Cianjur, Provinsi Jawa Barat) - Niken Hikmawati; Gema Wibawa Mukti (Hasanuddin University, 2018)
Indonesian society today does not show a great interest in the agricultural sector. Even though, there is one regency in West Java which have a highest population working in agricultural sector, that is Cianjur Regency. Agrofarm Cianjur is one of P4S (Pusat Pelatihan Pertanian dan Pedesaan Swadaya) in Cianjur Regency which do training cultivation and marketing of horticultural commodity, then there are farmers group which called Agro Segar. With the formation of Agrofarm Cianjur as a unity with different focus and function, it is important to look at the business model of Agrofarm Cianjur so it can be used as an inspiration for agricultural actors. This research uses qualitative research design with case study technique. The analytical tool used is value network mapping with Holo Mapping analysis and Business Model Canvas used to describe the applied business model. The description of business model is obtained through business design process with storytelling technique, visual thinking, and prototyping. Based on the results of research, business model of Agrofarm Cianjur is quite advanced and can be used as an inspiration for agricultural actors. Agrofarm Cianjur needs to add partners and resources, and update the administrative accounting which is still manual. Keywords: Canvas Business Model; Farmers Group; P4S; Value Network Mapping.